2017
DOI: 10.1371/journal.pone.0187751
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance parameters in a large population of game-ranched white rhinoceroses (Ceratotherium simum simum)

Abstract: The population of free-roaming white rhinoceroses (Ceratotherium simum) is under serious threat. Captive breeding of this species is therefore becoming more important, but this is challenging and often not successful. Obtaining reproductive reference values is a crucial aspect of improving these breeding results. In this study performed between 2008 and 2016, reproductive performance was analysed in 1,354 animals kept in a 8000 hectares game-ranched environment. Descriptive statistics of this captive populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…The average ACR and CI observed in this study were 18.6% and 3.7 years, respectively; which could be interpreted as a very poor fecundity population based on the guidelines provided by the Southern African Development Community Rhino Management Group (Du Toit 2006). The reproductive performance of the population in this study was less than that reported in other non-captive populations, for which ACR and CI ranged from 20 to 50% and 2.4 to 3.3 years, respectively (Rachlow and Berger 1998;Kretzschmar 2001;Ververs et al 2017). The ACR target is a value greater than 33%, which corresponds to a CI of 3 years (Du Toit 2006).…”
Section: Population Demographic Parametersmentioning
confidence: 59%
See 3 more Smart Citations
“…The average ACR and CI observed in this study were 18.6% and 3.7 years, respectively; which could be interpreted as a very poor fecundity population based on the guidelines provided by the Southern African Development Community Rhino Management Group (Du Toit 2006). The reproductive performance of the population in this study was less than that reported in other non-captive populations, for which ACR and CI ranged from 20 to 50% and 2.4 to 3.3 years, respectively (Rachlow and Berger 1998;Kretzschmar 2001;Ververs et al 2017). The ACR target is a value greater than 33%, which corresponds to a CI of 3 years (Du Toit 2006).…”
Section: Population Demographic Parametersmentioning
confidence: 59%
“…No evidence of natal sex-ratio skewness was found, which supports previous studies. Natal sex-ratio skewness toward males has been reported in captive SWRs (Zschokke et al 1998;Kretzschmar 2001;Linklater 2007), whereas non-captive populations kept at lower stocking densities have been reported to be in the expected 50:50 sex ratio (Ververs et al 2017). The average ACR and CI observed in this study were 18.6% and 3.7 years, respectively; which could be interpreted as a very poor fecundity population based on the guidelines provided by the Southern African Development Community Rhino Management Group (Du Toit 2006).…”
Section: Population Demographic Parametersmentioning
confidence: 93%
See 2 more Smart Citations
“…Thus, many breeding programmes have contributed to a better understanding of the extrinsic and intrinsic factors and requirements necessary for reproductive success, especially by documenting female reproductive physiology and performance [ 12 , 13 ]. However, for the context of captive breeding programmes, males play as equally an important role as females [ 14 , 15 ]. Thus, for species participating in conservation breeding programmes, a better understanding of the male reproductive behaviour and related physiology is crucial to optimise breeding efforts for threatened wildlife species.…”
Section: Introductionmentioning
confidence: 99%